Alienation for Reconciliation: Saving Iraq Displaced and Refugee Children - Aloose, Haider (International Journal of Language and Literary Studies, 2026)
This study examines the psychological trauma that continues to shape the minds of Iraqis and ?disrupt their behavior within educational environments. The problem emerges from decades of ?war, internal displacement, deprivation of basic needs, and the chronic absence of healthcare ?services, conditions locally expressed through the concept of Makoo, signifying prolonged scarcity ?and loss. Using the International Social Service (ISS) model for psychological rehabilitation and drawing conceptually on Noam Chomsky’s views on the reconstruction of displaced societies, the study analyzes how trauma reshapes children’s cognitive development, ethical awareness, and motivation toward schooling. Qualitative observations from displacement zones, particularly the Al-Hol camp, reveal that such environments metaphorically resemble “sterile land,” unable to foster stable learning, identity formation, or emotional growth. The findings suggest ?that educational decline in these regions is directly linked to accumulated psychological burdens. ?Accordingly, the study proposes developing idealized school-based micro-communities functioning ?as temporary protective institutions within these deteriorating environments that provide structured ?learning, psychological recovery, and moral stabilization. The results indicate that such specialized centers, though requiring targeted financial planning, could interrupt current cycles of deterioration and create pathways toward healthy reintegration and long-term educational resilience.?